Disorders of Consciousness in Hospitalized Patients with COVID-19: The Role of the Systemic Inflammatory Response Syndrome - Boehme, Amelia K.; Doyle, Kevin; Thakur, Kiran T.; Roh, David; Park, Soojin; Agarwal, Sachin; Velazquez, Angela G.; Egbebike, Jennifer A.; Der Nigoghossian, Caroline; Prust, Morgan L.; Rosenberg, Jon; Brodie, Daniel; et al. (Neurocritical care, 2022)
Background Prevalence and etiology of unconsciousness are uncertain in hospitalized patients with coronavirus disease 2019 (COVID-19). We tested the hypothesis that increased inflammation in COVID-19 precedes coma, independent of medications, hypotension, and hypoxia. Methods We retrospectively assessed 3203 hospitalized patients with COVID-19 from March 2 through July 30, 2020, in New York City with the Glasgow Coma Scale and systemic inflammatory response syndrome (SIRS) scores. We applied hazard ratio (HR) modeling and mediation analysis to determine the risk of SIRS score elevation to precede coma, accounting for confounders. Results We obtained behavioral assessments in 3203 of 10,797 patients admitted to the hospital who tested positive for SARS-CoV-2. Of those patients, 1054 (32.9%) were comatose, which first developed on median hospital day 2 (interquartile range [IQR] 1–9). During their hospital stay, 1538 (48%) had a SIRS score of 2 or above at least once, and the median maximum SIRS score was 2 (IQR 1–2). A fivefold increased risk of coma (HR 5.05, 95% confidence interval 4.27–5.98) was seen for each day that patients with COVID-19 had elevated SIRS scores, independent of medication effects, hypotension, and hypoxia. The overall mortality in this population was 13.8% ( n = 441). Coma was associated with death (odds ratio 7.77, 95% confidence interval 6.29–9.65) and increased length of stay (13 days [IQR 11.9–14.1] vs. 11 [IQR 9.6–12.4]), accounting for demographics. Conclusions Disorders of consciousness are common in hospitalized patients with severe COVID-19 and are associated with increased mortality and length of hospitalization. The underlying etiology of disorders of consciousness in this population is uncertain but, in addition to medication effects, may in part be linked to systemic inflammation.